Hydrogen in Ti and Zr alloys: industrial perspective, failure modes and mechanistic understanding. (28th July 2017) - Chapman, T. P.; Dye, D.; Rugg, D.
Abstract : Titanium is widely used in demanding applications, such as in aerospace. Its strength-to-weight ratio and corrosion resistance make it well suited to highly stressed rotating components. Zirconium has a no less critical application where its low neutron capture cross section and good corrosion resistance in hot water and steam make it well suited to reactor core use, including fuel cladding and structures. The similar metallurgical behaviour of these alloy systems makes it alluring to compare and contrast their behaviour. This is rarely undertaken, mostly because the industrial and academic communities studying these alloys have little overlap. The similarities with respect to hydrogen are remarkable, albeit potentially unsurprising, and so this paper aims to provide an overview of the role hydrogen has to play through the material life cycle. This includes the relationship between alloy design and manufacturing process windows, the role of hydrogen in degradation and failure mechanisms and some of the underpinning metallurgy. The potential role of some advanced experimental and modelling techniques will also be explored to give a tentative view of potential for advances in this field in the next decade or so. This article is part of the themed issue 'The challenges of hydrogen and metals'.